Fire Spalling Prevention via Polypropylene Fibres: A Meso- and Macroscale Approach. (22nd August 2016) - Mazzucco, G.; Xotta, G.
Abstract : A deep understanding of concrete at the mesoscale level is essential for a better comprehension of several concrete phenomena, such as creep, damage, and spalling. The latter one specifically corresponds to the separation of pieces of concrete from the surface of a structural element when it is exposed to high and rapidly rising temperatures; for this phenomenon a mesoscopic approach is fundamental since aggregates performance and their thermal properties play a crucial role. To reduce the risk of spalling of a concrete material under fire condition, the inclusion of a low dosage of polypropylene fibres in the mix design of concrete is largely recognized. PP fibres in fact evaporate above certain temperatures, thus increasing the porosity and reducing the internal pressure in the material by an increase of the voids connectivity in the cement paste. In this work, the contribution of polypropylene fibres on concrete behaviour, if subjected to elevated thermal ranges, has been numerically investigated thanks to a coupled hygrothermomechanical finite element formulation. Numerical analyses at the macro- and mesoscale levels have been performed.